Emerging nanoelectronic devices - Chen, An (Electronics engineer); Hutchby, James; Zhirnov, Victor V., editor; Bourianoff, George (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
Includes bibliographical references and index